Food and human gut as reservoirs of transferable antibiotic resistance encoding genes - Rolain, Jean-Marc (Frontiers in Microbiology, 2013)
The increase and spread of antibiotic resistance (AR) over the past decade in human pathogens has become a worldwide health concern. Recent genomic and metagenomic studies in humans, animals, in food and in the environment have led to the discovery of a huge reservoir of AR genes called the resistome that could be mobilized and transferred from these sources to human pathogens. AR is a natural phenomenon developed by bacteria to protect antibiotic-producing bacteria from their own products and also to increase their survival in highly competitive microbial environments. Although antibiotics are used extensively in humans and animals, there is also considerable usage of antibiotics in agriculture, especially in animal feeds and aquaculture. The aim of this review is to give an overview of the sources of AR and the use of antibiotics in these reservoirs as selectors for emergence of AR bacteria in humans via the food chain.